Isolation and characterization of partial gene sequence encoding for UDP- sugar pyrophosphorylase (USPase) from kelampayan (Neolamarckia cadamba) - Lee, Vivian (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Neolamarckia cadamba, or locally known as Kelampayan, has emerged as an important tree species in plantation forestry as it is believed to hold the promise for sustainable harvesting of forest in the future due to its fill t-growing property and its ability to produce wood for various economic uses. UDP-sugar pyrophosphorylase (USPase), also known as UTP-monosaccharide-l-phosphate uridyltransferase, is believed to playa role in Kelampayan wood fonnation due to its enzymatic function in plant carbohydrate metaboli m which is involved in cell wall synthesis. The aim of this study is to isolate and characterize partial USPase gene of Kelampayan. Total RNA was isolated from developing xylem of Kelampayan and then reverse transcribed to cDNA, which was amplified using reverse transcription-PCR (RT-PCR) approach. Genomic DNA was also extracted from leaf tissues to isolate the gene. The isolated partial genes from both cDNA and gDNA were sequenced and subsequently subjected to in-silico characterization. Sequence homology search at nucleotide level showed no matching identity between partial gene sequence of Kelampayan USPase and USPase characterized in other plant species.